Islamic Feminism in Indonesia: An Analysis of the Discourse on Gender Equality by the ‘Ulama Perempuan’ (Female Ulama) Congress - Zakka, Umar; Nizam, Zain; Farah, Rina (Yayasan Adra Karima Hubbi, 2025)
Background. The emergence of Islamic feminism in Indonesia represents a significant redefinition of gender discourse within an Islamic framework. This study explores how the Kongres Ulama Perempuan Indonesia (KUPI) constructs and disseminates ideas of gender equality rooted in Qur’anic hermeneutics, Islamic jurisprudence, and social justice principles. Purpose. The research aims to analyze the theological, sociocultural, and political narratives articulated by female ulama to promote gender-inclusive interpretations of Islam. Method. Using a qualitative approach based on critical discourse analysis, the study examines official congress documents, public sermons, and media statements produced during and after the congress sessions (2017–2022). Results. The findings reveal that KUPI reframes gender equality not as a Western liberal import but as an authentic Islamic ethical imperative grounded in rahmatan lil ‘alamin values. Female ulama reinterpret classical texts to challenge patriarchal readings and advocate for women’s leadership, protection from gender-based violence, and equitable religious authority. Conclusion. The study concludes that Islamic feminism in Indonesia represents a contextualized form of theological activism that bridges Islamic scholarship, social advocacy, and policymaking, thereby expanding the epistemological boundaries of gender justice within the Muslim world.